The Role of Nurses in Infectious Solid Waste Management: A Narrative Review - Widodo, Dhito; Romadhon, Yusuf Alam; Praswati, Aflit (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Background: The management of infectious solid waste is essential in healthcare, influencing environmental safety and public health. Nurses, as frontline healthcare practitioners, are integral to the management of medical waste, encompassing segregation, storage, and disposal. Efficient waste management mitigates the risk of infections and environmental pollution; nonetheless, nurses may encounter difficulties stemming from inadequate training, limited resources, and exposure to work dangers. Aim: This narrative review analyzes the roles of nurses in the management of infectious solid waste, their contributions to patient safety, and the problems encountered in executing good waste management techniques. Methods: A narrative review was performed utilizing academic sources (PubMed, Scopus, Google Scholar) to discover research on nurses' roles, education, and difficulties in hospital waste management. Studies were chosen for their pertinence to waste management techniques within healthcare environments. Results: Nurses are essential in the secure segregation, storage, and disposal of infectious waste. They mitigate infection risks by guaranteeing accurate classification and secure waste containment. Challenges such as limited resources, insufficient training, excessive workloads, and exposure to occupational risks impede effective waste management, despite its crucial importance. Nurses assist to infection prevention by implementing proper hygiene practices and utilizing personal protective equipment (PPE).